2002
DOI: 10.1017/s0022029902005472
|View full text |Cite
|
Sign up to set email alerts
|

Thermal inactivation of chymosin during cheese manufacture

Abstract: The aspartic proteinase, chymosin (EC 3.4.23.4) is the principal milk clotting enzyme used in cheese production and is one of the principal proteolytic agents involved in cheese ripening. Varietal differences in chymosin activity, due to factors such as cheese cooking temperature, fundamentally influence cheese characteristics. Furthermore, much chymosin is lost in whey, and further processing of this by-product may require efficient inactivation of this enzyme, with minimal effects on whey proteins. In the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 15 publications
2
34
0
Order By: Relevance
“…Rather higher levels of residual chymosin have been found in the hard type cheeses, in which the cooking conditions are in general milder and the salt content higher than that in Gruyere type cheeses (Table 1). Hayes et al (2002) have found that in both Cheddar and Emmental curd pieces and 1-day-old cheeses, the residual chymosin activity was similar, contrast to the decreased chymosin-induced proteolysis observed during storage of Swiss cheese slurry. It has been reported that during cooking at temperatures up to 55°C, the enzyme is partially and reversibly denatured and can be partially reactivated during ripening (Hayes et al 2002(Hayes et al , 2004.…”
Section: Residual Chymosin Activitymentioning
confidence: 81%
See 2 more Smart Citations
“…Rather higher levels of residual chymosin have been found in the hard type cheeses, in which the cooking conditions are in general milder and the salt content higher than that in Gruyere type cheeses (Table 1). Hayes et al (2002) have found that in both Cheddar and Emmental curd pieces and 1-day-old cheeses, the residual chymosin activity was similar, contrast to the decreased chymosin-induced proteolysis observed during storage of Swiss cheese slurry. It has been reported that during cooking at temperatures up to 55°C, the enzyme is partially and reversibly denatured and can be partially reactivated during ripening (Hayes et al 2002(Hayes et al , 2004.…”
Section: Residual Chymosin Activitymentioning
confidence: 81%
“…Hayes et al (2002) have found that in both Cheddar and Emmental curd pieces and 1-day-old cheeses, the residual chymosin activity was similar, contrast to the decreased chymosin-induced proteolysis observed during storage of Swiss cheese slurry. It has been reported that during cooking at temperatures up to 55°C, the enzyme is partially and reversibly denatured and can be partially reactivated during ripening (Hayes et al 2002(Hayes et al , 2004. Moreover, according to Hayes et al (2001), residual chymosin activity in high-cooked cheeses may be partially attributed to cathepsin D, which is less heat-labile than chymosin and hydrolyses the assay substrate similarly to chymosin under the same conditions.…”
Section: Residual Chymosin Activitymentioning
confidence: 81%
See 1 more Smart Citation
“…Chymosin is the principle enzyme responsible for milk coagulation (Hayes et al, 2002) and is essential for cheese ripening (Fox and Law, 1991). Rennet cleaves κ-CN at the Phe 105 -Met 106 bond, resulting in a para-κ-CN and a hydrophilic glycomacropeptide (Visser, 1993;Hayes et al, 2002) as shown in Figure 5.…”
Section: Coagulantsmentioning
confidence: 99%
“…Rennet cleaves κ-CN at the Phe 105 -Met 106 bond, resulting in a para-κ-CN and a hydrophilic glycomacropeptide (Visser, 1993;Hayes et al, 2002) as shown in Figure 5. As mentioned earlier, chymosin causes the initial softening of cheese where the breakdown of α s1 -CN to α s1 -I-CN takes place (Creamer and Olson, 1982;Sheehan et al, 2007;Feeney et al, 2002).…”
Section: Coagulantsmentioning
confidence: 99%